Influência do estresse hídrico, riqueza e abundância de espécies nativas sobre o potencial invasor de uma Poaceae exótica - MICHELAN, Thaísa Sala (2011)
Exotic species represent strong threats to biodiversity. This concern is especially valid in freshwater ecosystems due to their high biodiversity and the highest rates of extinction, compared with terrestrial and marine ecosystems. The increasing habitat complexity provided by the presence of macrophytes may partially explain the high diversity of aquatic ecosystems. However, depending on the density and other particular characteristics of these plant, the diversity may be negatively affected. In this context, Urochloa subquadripara, a species native to Africa, is an aquatic macrophyte weed occurring in various natural and artificial aquatic ecosystems in America. In a small scale, the occurrence of this exotic species increases with reducing natives species richness; however, in a large scale U. subquadripara invades sites with more richness of native species. This controversy is typical of observational studies in invasion biology and it demand experiments to test effects of abiotic and biotic resistance on the invasive potential of this exotic. Accordingly, two experiments were conducted in order to test the following hypotheses: (i) the regeneration and colonization of U. subquadripara decreases with increasing time of exposure to dry, (ii) fragments of the apical part of this species, when compared with those of the basal part, have higher viability and colonization potential (first experiment) and (iii) the invasiveness of aquatic environments by U. subquadripara is negatively influenced by the richness and abundance of native species (second experiment). Our results supported all of our hypotheses: U. subquadripara showed high resistance to desiccation, and the fragments of the apical part were those which had higher viability and colonization potential. In addition, both richness and abundance of native species affected negatively the invasive potential of this exotic macrophyte. The second experiment demonstrated that the effect of richness and abundance limited the development of U. subquadripara, although such effect was not sufficient to prevent the invasion of macrophyte communities by this species. Based on these results, it appears that the population growth of U. subquadripara is greater in disturbed sites, mainly those affected by drought, which in general, have lower abundance and diversity of native species.